Effect of an Intensive Multi-Modal Intervention for Attention-Deficit Hyperactivity Disorder (ADHD) on Equity in Children’s Health and Educational Outcomes: IJPDS (2017) Issue 1, Vol 1:008, Proceedings of the IPDLN Conference (August 2016) - Smith, Mark; Chateau, Dan; Enns, Jennifer; Randall, Jason; Bolton, James; Katz, Laurence; Burland, Elaine; Katz, Alan; Brownell, Marni; Raymond, Collette (International Journal of Population Data Science, 2017)
ABSTRACT Objectives To determine whether an intensive multi-modal ADHD intervention for children and teens resulted in improved long-term health and educational outcomes and in reduced inequity in these outcomes across the socioeconomic gradient. Approach We used administrative data from the healthcare and education sectors in the Population Health Data Repository at the Manitoba Centre for Health Policy. We identified children and teens aged 5-17 who had 3+ visits to the ADHD intervention program between 2007 and 2012. A matched control group was constructed, and confounders were controlled using inverse probability of treatment weights. We examined rates of hospital episodes, emergency department visits, psychostimulant use and adherence, contact with child and family services, and whether the children were in the school grade appropriate to their age. We calculated concentration indices to measure changes in inequity. Results There were 485 children in the ADHD intervention group and 1,884 controls. Children who received the intervention were more likely to be prescribed medication (patients with 1+ prescription(s), rate ratio [RR] 1.21, 95% CI 1.08-1.36) and be adherent to their medication (RR 1.42, 95% CI 1.03-1.96). They were also more likely to be in their age-appropriate grade (RR 1.33, 95% CI 1.09-1.63) compared to controls. Moreover, the intervention was associated with reduced inequity in these outcomes across income deciles. No difference in the rates of hospital episodes or emergency department visits was found, nor in rates of contact with child and family services. Conclusions A multi-modal ADHD intervention program was associated with increased use and adherence to medication, and may boost academic achievement for vulnerable children and teens. It contributed to closing the equity gap between children from low- and high-income families. ADHD interventions that combine approaches may be more effective than medication alone.